2015
DOI: 10.1016/j.jhazmat.2015.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Allochthonous bioaugmentation in ex situ treatment of crude oil-polluted sediments in the presence of an effective degrading indigenous microbiome

Abstract: 28"Oil-polluted sediment bioremediation depends on both physicochemical and 29" biological parameters, but the effect of the latter cannot be evaluated without the optimization 30" of the former. We aimed in optimizing the physicochemical parameters related to 31" biodegradation by applying an ex-situ landfarming set-up combined with biostimulation to 32" oil-polluted sediment, in order to determine the added effect of bioaugmentation by four 33" allochthonous oil-degrading bacterial consortia in relation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…DNA was quantified using NanoDrop 1000 spectrophotometer (Thermo Scientific, Waltham, MA, USA). The ARISA fingerprinting was obtained using the primer set ITSF, 5′-GTCGTAACAAGGTAGGCCGTA-3′ and ITSReub, 5′-GCCAAGGCATCCACC-3′, as described elsewhere (Cardinale et al, 2004; Fodelianakis et al, 2015). The output peak matrix was transferred to Microsoft Excel for the following analysis.…”
Section: Methodsmentioning
confidence: 99%
“…DNA was quantified using NanoDrop 1000 spectrophotometer (Thermo Scientific, Waltham, MA, USA). The ARISA fingerprinting was obtained using the primer set ITSF, 5′-GTCGTAACAAGGTAGGCCGTA-3′ and ITSReub, 5′-GCCAAGGCATCCACC-3′, as described elsewhere (Cardinale et al, 2004; Fodelianakis et al, 2015). The output peak matrix was transferred to Microsoft Excel for the following analysis.…”
Section: Methodsmentioning
confidence: 99%
“…When they are added into contaminated sites, they cannot easily integrate and adapt to the activities of the indigenous microbial community. Fodelianakis et al [38] confirmed that bioaugmentation with allochthonous hydrocarbon-degrading bacterial consortia did not enhance the remediation process of hydrocarbon-contaminated sediments. Thus, the application of autochthonous microorganism is more effective [35].…”
Section: Bioaugmentationmentioning
confidence: 99%
“…The ABA approach consists on the addition of autochthonous microbial isolates or consortia that are adapted to the contaminated environments [37]. Different studies confirmed the efficiency of autochthonous microorganisms in the decontamination of hydrocarbon-polluted sites based on the fact that environmental conditions are suitable for their growth and metabolism [36,38]. They significantly contribute to the biochemical activities in soil.…”
Section: Bioaugmentationmentioning
confidence: 99%
See 2 more Smart Citations